2012
DOI: 10.1080/00288306.2012.671181
|View full text |Cite
|
Sign up to set email alerts
|

Marine submersion of an archaic moa-hunter occupational site, Shag River estuary, North Otago

Abstract: At Shag River estuary, North Otago, New Zealand, parts of an Archaic moa-hunter occupation site (AD 1340Á1410) lie beneath 50 cm of saltmarsh sediment at a modern elevation of 0.3 m below mean high water. Fossil saltmarsh foraminiferal assemblages in the overlying cored sediment provide high-tidal palaeo-elevation estimates (Modern Analogue Technique) that indicate a gradual rise in relative sea level of 0.5990.05 m since that time. This part of the moa-hunter site appears to have been located on an unvegetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…As well as being few in number, existing proxy-based late Holocene RSL records from the south-west Pacific rely on limited quantification of the contemporary relationship between microfossil distributions and elevation above sea level (Gehrels et al, 2008(Gehrels et al, , 2012Figueira, 2012;Grenfell et al, 2012;Hayward et al, 2012). A comprehensive understanding of the elevation-dependent zonation of microfossils, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As well as being few in number, existing proxy-based late Holocene RSL records from the south-west Pacific rely on limited quantification of the contemporary relationship between microfossil distributions and elevation above sea level (Gehrels et al, 2008(Gehrels et al, , 2012Figueira, 2012;Grenfell et al, 2012;Hayward et al, 2012). A comprehensive understanding of the elevation-dependent zonation of microfossils, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In Mur 1, 4 and 5, a rapid upcore increase in organic matter and a switch from mid-low tidal Am faunas to Hw and Tn high tidal salt marsh faunas at c. 80 cm could record a co-seismic uplift but we infer it is caused by a rapid eustatic fall in sea level at the start of the Little Ice Age c. 600 years ago, as recorded elsewhere around New Zealand (Figueira 2012;Hayward, Grenfell et al 2012a). The rapid subsidence at the top of these cores has been caused by compaction of the upper layer of organic-rich sediment due to an induced lowering of groundwater levels following the construction of a stop bank c. 50 years ago.…”
Section: Muriwai Wherowhero Lagoon Coresmentioning
confidence: 80%
“…BL13-2 was cored in high tide marsh at 1.4 m elevation, which with projected sediment accumulation gives a further ,0.5 m of relative subsidence during deposition of the upper 50 cm of the cored sequence. Several recent studies along the east coast of the South Island of New Zealand (Gehrels et al, 2008;Figueira, 2012;Hayward et al, 2012) have concluded that sea-level rose ,60 cm in the last 400-600 years and thus we infer that it was eustatic sea-level rise and not seismic events or autocompaction that was responsible for the elevational record in the upper part of BL13-2. Core BL72 was taken at the top of the lagoon beach at 1.0 m elevation, giving an estimated ,0.55 m of inferred sea-level rise recorded in the upper 30-50 cm of this section in the last 500 yrs.…”
Section: Inferred Elevational and Paleoenvironmental Historymentioning
confidence: 90%
“…This is inferred to be the result of progressive and accelerating eustatic sealevel rise of approximately this amount over the last 500-600 years (e.g., Hayward et al, 2012).…”
Section: Inferred Co-seismic Displacement Events In Big Lagoon Coresmentioning
confidence: 98%